Perovskite solar cell modified by inorganic passivation layer and preparation method thereof

The lead sulfate-lead oxide inorganic passivation layer formed by using strong oxidizing ammonium persulfate inorganic salts in perovskite solar cells has been solved, and the photoelectric conversion efficiency and stability of the device are significantly improved.

CN119789668AActive Publication Date: 2025-04-08上虞半导体材料研究中心

Patent Information

Application Number
CN202411634762.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-04-08
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

In existing perovskite solar cells, the use of organic small molecule passivators has problems such as poor stability and easy desorption, which leads to re-exposed perovskite surface defects, affecting the long-term stability and efficiency of the device.

Method used

The lead sulfate-lead oxide inorganic passivation layer formed by strong oxidizing ammonium persulfate inorganic salt is modified by spin coating and annealing technology to form a dense inorganic passivation layer to improve the stability of the perovskite surface.

Benefits of technology

The photoelectric conversion efficiency, open circuit voltage, short circuit current and photovoltaic performance parameters of perovskite solar cells are significantly improved, while the photothermal stability of the device is enhanced, solving the stability problem of organic small molecule passivator.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119789668A_ABST
    Figure CN119789668A_ABST
Patent Text Reader

Abstract

According to the inorganic passivation layer modified perovskite solar cell and the preparation method thereof, the compact lead sulfate-lead oxide inorganic layer is further formed through surplus lead iodide on the surface of calcium perovskite with strong oxidizing property to passivate the perovskite thin film, and the efficient and stable perovskite cell is prepared. According to the invention, the perovskite thin film is processed by using the passivator solution, and the photoelectric conversion efficiency of the prepared device can reach 24.98% at most. Meanwhile, the perovskite thin film treated by the passivator has excellent photo-thermal stability. According to the perovskite device prepared by the method, the passivation effect is remarkable, the waterproof performance of the perovskite material is remarkably improved, and the method has important significance in performance improvement and commercialized production of perovskite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of perovskite cells, and in particular relates to a perovskite solar cell modified with an inorganic passivation layer and a preparation method thereof. Background Art

[0002] Perovskite solar cells have attracted widespread attention in the field of solar cells due to their advantages such as large absorption coefficient, wide absorption range, and high conversion efficiency. At present, the research on perovskite solar cells mainly uses small organic molecules to treat the surface of perovskite to achieve the purpose of passivation defects. These small organic molecules are not stable in themselves, and they are easily decomposed when exposed to water and oxygen, and they will react with the perovskite itself. When these small molecules are introduced into the perovskite surface after post-treatment, due to weak interactions between organic matter or weak chemical bonds, they may desorb from the perovskite under long-term placement or operation, causing defects to be exposed again; they may also migrate to the perovskite phase, causing deeper degradation of the perovskite. Therefore, how to solve the problems caused by the passivation treatment of small organic molecules and prepare efficient and stable perovskite devices at the same time is a technical problem that needs to be solved urgently. Summary of the invention

[0003] In view of the problems existing in the prior art, the purpose of the present invention is to provide a perovskite solar cell modified with an inorganic passivation layer and a preparation method, which is specifically achieved through the following technical solutions:

[0004] A perovskite solar cell modified with an inorganic passivation layer, the perovskite solar cell comprises a positive substrate, a hole transport layer, a perovskite active layer, an active layer interface modification layer, an electron transport layer, a cathode modification layer and a cathode which are sequentially arranged from bottom to top, wherein the active interface modification layer is an inorganic passivation layer formed by an ammonium persulfate inorganic salt spin-coated on the perovskite active layer.

[0005] Furthermore, the inorganic passivation layer is a lead sulfate-lead oxide inorganic passivation layer formed by oxidation of ammonium sulfate.

[0006] Furthermore, the thickness of the hole transport layer is 5-15nm, the thickness of the perovskite active layer is 600-700nm, the thickness of the active layer interface modification layer is 5-20nm, the thickness of the electron transport layer is 40-80nm, the thickness of the cathode modification layer is 1-6nm, and the thickness of the cathode is 120nm.

[0007] Furthermore, the active layer interface modification layer is obtained by dissolving ammonium persulfate in isopropyl alcohol IPA and trifluoroethanol TF-EtOH to form a saturated solution at room temperature, and then spin-coating it on the perovskite active layer and annealing it at 100° C. for 5 minutes.

[0008] A method for preparing a perovskite solar cell modified with an inorganic passivation layer comprises the following steps:

[0009] A positive substrate is selected and cleaned, and a hole transport layer, a perovskite active layer, and an active layer interface modification layer are spin-coated on the positive substrate from bottom to top, and an electron transport layer, a cathode modification layer, and a cathode are evaporated; wherein the active layer interface modification layer is a dense inorganic passivation layer of lead sulfate and lead oxide formed by spin-coating the strong oxidizing inorganic salt ammonium persulfate on the perovskite active layer to oxidize the excess lead iodide on the perovskite surface.

[0010] The positive substrate is a flexible or rigid substrate on which a uniform indium tin oxide ITO layer, FTO layer, Si layer, or CIGS layer is deposited. In a preferred embodiment of this scheme, the positive substrate is a flexible or rigid substrate on which a layer of indium tin oxide ITO layer is deposited, and the thickness of the indium tin oxide ITO layer is 100 nm.

[0011] Further, the hole transport layer is one of 2-pyrenyl-ethyl phosphoric acid, 2-(9H-carbazole-9-yl)ethylphosphonic acid, 2-(3,6-dimethoxy-9H-carbazole-9-yl)ethylphosphonic acid, and 4-(3,6-dimethyl-9H-carbazole-9-yl)butylphosphonic acid, which is spin-coated on the anode substrate. Preferably, 2-(9H-carbazole-9-yl)ethylphosphonic acid is dissolved in ethanol to form a solution with a mass concentration of 0.6 mg / mL, and then a 2-(9H-carbazole-9-yl)ethylphosphonic acid film with a thickness of 5-15 nm is prepared by solution spin coating.

[0012] Furthermore, the perovskite active layer is prepared by a one-step spin coating method of a perovskite precursor solution and combined with an annealing treatment process. Specifically, after obtaining the perovskite precursor solution, a liquid phase one-step spin coating method is used to spin coat it on a flexible or rigid substrate with a carrier transport layer. After the spin coating is completed, it is heated at 120°C for 30 minutes.

[0013] Furthermore, the electron transport layer is a C60 film, a PCBM film, a SnO film deposited on the interface modification layer of the active layer. x In a preferred embodiment of this scheme, the thickness of the electron transport layer is 45-60nm. In addition, the thickness of the perovskite active layer is 600-700nm, the thickness of the active layer interface modification layer is 5-10nm, the thickness of the hole transport layer is 10nm, the thickness of the cathode modification layer is 6-10nm, and the thickness of the cathode is 120nm.

[0014] Furthermore, the negative modification layer is a BCP deposited on the electron transport layer, and the cathode is a gold film or a silver film vacuum-thermally evaporated on the hole transport layer.

[0015] The perovskite active layer is prepared by a one-step spin coating method of a perovskite precursor solution and combined with an annealing process. In the preparation step of the perovskite precursor solution, the A site uses a mixed ratio of FA (formamidinium ion), MA (methylamine ion), and Cs (cesium ion); X is the same I (iodine), Br (bromine), Cl (chlorine) or different halogen ions of I, Br, and Cl; the precursor solution selects a solvent that can dissolve the perovskite material, such as DMF, DMSO, γ-butyrolactone, IPA, and CB. In this scheme, AX is selected as FAI, MACl, FABr, MABr, FACl or MAI, preferably FAI and MABr.

[0016] The dense inorganic layer formed by the redox reaction between the strong oxidizing inorganic salt and the excess lead iodide on the surface of the perovskite is used as the active layer interface modification layer between the perovskite active layer and the electron transport layer. The advantages of this are: on the one hand, it plays a role in regulating the interface energy level and passivating the surface defects of the perovskite layer, thereby improving the photothermal stability of the perovskite layer; on the other hand, it solves the problem that the organic small molecule passivator itself has poor stability and is easy to desorb, causing the defects to be exposed again. The present application uses the inorganic passivation layer obtained by oxidation of the strongly oxidizing ammonium persulfate molecule as a modification layer, which is modified on the already formed perovskite active layer to post-treat the perovskite film, and does not affect the crystallization process of the perovskite film; and the inorganic passivation layer of the present application has the characteristics of N-type doping, which can not only improve the stability of the perovskite battery, but also further improve the photoelectric conversion efficiency.

[0017] The structure of strongly oxidizing ammonium persulfate inorganic salt is as follows:

[0018]

[0019] The above scheme solves the problem of the instability of common organic small molecule passivators themselves, while improving the performance and stability of the device. Compared with the efficiency of the reference device without interface modification of 23.25%, the photoelectric conversion efficiency of the device modified with the inorganic passivation layer is increased to 24.98%, while the photovoltaic performance parameters such as the open circuit voltage (Voc), short circuit current (Jsc) and photoelectric conversion efficiency (PCE) of the device are improved. More importantly, compared with traditional organic small molecule passivators, the performance of the device treated with strongly oxidizing ammonium persulfate shows superior photothermal stability. The manufacturing process of the present invention is simple and suitable for industrial large-scale production of perovskite devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The present invention provides a battery structure of an inorganic passivation layer modified perovskite battery;

[0021] Figure 21 is a scanning electron micrograph (SEM) of the surface of the formamidinium lead iodide perovskite film modified with and without ammonium persulfate modification; wherein a is a SEM image of the surface of the unmodified perovskite film, and b is a SEM image of the surface of the perovskite film treated with a saturated ammonium persulfate isopropanol solution;

[0022] Figure 3 It is the rapid imaging of steady-state photoluminescence spectra (PL mapping) on ​​the surface of ammonium persulfate-modified and unmodified formamidinium lead iodide perovskite films;

[0023] Figure 4 The X-ray diffraction (XRD) changes of ammonium persulfate modified and unmodified perovskite films after heating at 85°C in a glove box for 48 hours and 96 hours and placing in air with a relative humidity of 65% for 48 hours and 96 hours;

[0024] Figure 5 These are the optimal voltage curves and device parameters of ammonium persulfate modified and unmodified perovskite solar cells. DETAILED DESCRIPTION

[0025] The present invention is further described below in conjunction with specific embodiments.

[0026] Example 1

[0027] Preparation of self-oxidized inorganic passivation layer modified perovskite cell by surface self-oxidation with ammonium persulfate to form an inorganic passivation layer:

[0028] A formamidinium cesium lead iodide perovskite solar cell containing a sulfate inorganic passivation interface modification layer has a device structure of ITO / 2PACz / FA0.95Cs0.05PbI3 / inorganic passivation layer / C60 / BCP / Ag, an ITO anode with a thickness of 100 nm and a sheet resistance of 15Ω. Before use, the ITO anode is ultrasonically cleaned with deionized water, acetone, and isopropanol in sequence, and then dried with nitrogen and the ITO surface is treated with a plasma cleaner for 25 minutes. The hole transport layer 2PACz has a thickness of 5 nm and is spin-coated on the ITO layer in a nitrogen glove box (H2O and O2 contents are both less than 1ppm), and then annealed. The spin coating rate is 3000 rpm, the spin coating time is 40 seconds, the annealing temperature is 110°C, and the annealing time is 20 minutes. 70 microliters of FA0.95Cs0.05PbI3 precursor solution was dripped onto the 2PACz film, and the film was spin-coated for 50 seconds at a speed of 5000 rpm. At the countdown of 10 seconds, 200 microliters of chlorobenzene (CB) was uniformly dripped, and a 700 nm thick perovskite active layer was obtained in combination with annealing. The molar concentration of the FA0.95Cs0.05PbI3 precursor solution is 1.7M, wherein lead iodide is additionally excessive by 5%, the volume ratio of DMF and DMSO in the mixed solvent of N, N-dimethylformamide DMF and dimethyl sulfoxide DMSO is 5:1, and an additional 15% MACl is added to the precursor solution as an additive. At room temperature, the prepared mixed solution is placed on a magnetic stirrer and stirred until completely dissolved. The perovskite film preparation method is: the above-mentioned clear solution is spin-coated on a flexible or rigid substrate with a carrier transport layer by a liquid phase one-step spin coating method, and after the spin coating is completed, it is heated at 120°C for 30 minutes.

[0029] The inorganic passivation layer is prepared by dissolving ammonium persulfate in a mixed solution of isopropyl alcohol IPA and trifluoroethanol (v / v=1:2) to form a saturated solution, filtering it, and then annealing it using a solution spin coating method. The film thickness is 5-10nm. The preparation method of the PC61BM electron transport layer of the battery structure is: the solvent of the precursor solution is CB, and 20mg / mL of the PC61BM precursor solution is spin coated on the perovskite layer in a nitrogen atmosphere glove box to obtain an electron transport layer with a thickness of 60nm. No annealing is required, the spin coating rate is 3000rpm, and the spin coating time is 30s. The cathode modification layer BCP in the battery structure is prepared by a vacuum thermal evaporation method. The film thickness is 6nm and the evaporation rate is

[0031] The structure of the perovskite battery prepared above is as follows Figure 1 shown.

[0032] Control group 1

[0033] In the control group 1, no ammonium persulfate solution oxidation modification was performed, and other conditions were the same as those in Example 1.

[0034] Example 2

[0035] 1) Prepare 1.70M FA at room temperature 0.95 Cs 0.05 PbI3 perovskite precursor solution was stirred on a magnetic stirrer until completely dissolved;

[0036] 2) Spin coating the clear solution onto a quartz substrate using a liquid phase one-step spin coating method, and after the spin coating is completed, heat at 110° C. for 30 minutes;

[0037] 3) Ammonium persulfate is dissolved in a mixed solution of isopropyl alcohol (IPA) and trifluoroethanol (v / v=1:2) to form a saturated solution, which is then filtered and then treated on the perovskite film by a solution spin coating method and annealed at 100°C for 5 minutes.

[0038] Control group 2

[0039] No modification was performed in the control group 2, and other conditions were the same as those in Example 2.

[0040] Effect detection:

[0041] (1)Perovskite device performance test

[0042] Photoelectric conversion test was conducted under AAA-level solar simulator with a test step length of 5ms and an effective area of ​​0.1cm 2 , the bias voltage is from -0.2 to 1.2V or 1.2 to -0.2V.

[0043] like Figure 5 It can be seen that the photoelectric conversion efficiency of the perovskite device obtained in Example 1 containing the lead sulfate-lead oxide inorganic passivation layer is as high as 24.98%, and the maximum photoelectric conversion efficiency of the unmodified perovskite device in the control group 1 is 23.25%. It can be seen that the photoelectric conversion efficiency of the perovskite device containing the lead sulfate-lead oxide inorganic passivation layer is significantly improved.

[0044] (2) Test of calcium peptide mineral film morphology:

[0045] This scheme uses a scanning electron microscope test device to observe the perovskite films obtained in Example 2 and Control Group 2 under ultra-high vacuum. Figure 2 a and 2b correspond to the electron microscopy images of the perovskite films of the control group 2 and example 2, respectively.

[0046] from Figure 2 It can be seen that compared with the perovskite film of the control group 2, the film of Example 2 in which the perovskite surface was oxidized did not undergo significant changes, which means that the strongly oxidizing ammonium persulfate solution did not destroy the perovskite surface, thereby ensuring the structural stability of the perovskite film.

[0047] Using the steady-state fluorescence spectrometer for rapid imaging, the PL mapping image is as follows: Figure 3 As shown, from Figure 3 It can be seen that compared with the perovskite film of the control group 2, the film of Example 2 has a significantly stronger intensity of surface photoluminescence, and the fluorescence of the two-dimensional spectrum is more homogeneous, which means that there are fewer defects on the surface of the film as a whole.

[0048] Combining the two surface morphology test methods, we can conclude that after the perovskite film of Example 2 is oxidized by ammonium sulfate, the surface of the film does not undergo obvious changes, while the defects on the surface of the perovskite are significantly reduced.

[0049] (3) X-ray polycrystal diffraction test:

[0050] The perovskite films obtained in Example 2 and Control Group 2 were tested under the same conditions using X-ray polycrystalline diffraction. Figure 4 shown. Figure 4 The film crystal structure diagrams of Example 2 and Control Group 2 were obtained by X-ray polycrystalline diffraction test after humidity aging and high temperature aging, respectively.

[0051] Depend on Figure 4 It can be seen that the humidity stability comparison is a comparison of 48 hours and 96 hours at 65% relative humidity. In the initial state, the films of Control Group 2 and Example 2 did not have a peak at 12.7°, indicating that the lead iodide on the surface of the perovskite was not exposed in large quantities. After being placed for 48 hours and 96 hours, the XRD spectrum of Control Group 2 showed that a large amount of lead iodide was produced, and its diffraction intensity continued to increase with water vapor erosion; in contrast, the perovskite film of Example 2 treated with ammonium sulfate had almost no peak near 12.7°, and still maintained a good film state without decomposition. Therefore, it is concluded that after the ammonium persulfate treatment, the film that forms the inorganic passivation layer of lead sulfate-lead oxide has excellent moisture resistance. The invasion of water vapor is an important reason for the performance degradation of perovskite solar cells under working conditions.

[0052] The comparison of thermal stability is carried out in a nitrogen atmosphere glove box, with continuous heating at 85°C. In the initial state, the films of Control Group 2 and Example 2 have no peak at 12.7°, indicating that the lead iodide on the surface of the perovskite is not exposed in large quantities. After heating for 48 hours and 96 hours, the XRD spectrum of Control Group 2 shows an enhanced peak at 12.7°, representing the exposure of a large amount of lead iodide, which indicates that the perovskite continues to degrade during the heating process, resulting in the generation of lead iodide. In contrast, the film of Example 2, which forms an inorganic passivation layer after being treated with ammonium sulfate, has a significantly improved degree of degradation.

Claims

1. A perovskite solar cell modified with an inorganic passivation layer, characterized in that The perovskite solar cell comprises a positive substrate, a hole transport layer, a perovskite active layer, an active layer interface modification layer, an electron transport layer, a cathode modification layer and a cathode which are arranged in sequence from bottom to top. The active interface modification layer is an inorganic passivation layer formed by an inorganic ammonium persulfate salt spin-coated on the perovskite active layer.

2. The inorganic passivation layer modified perovskite solar cell according to claim 1, characterized in that The inorganic passivation layer is a lead sulfate-lead oxide inorganic passivation layer formed by oxidation of ammonium sulfate.

3. The inorganic passivation layer modified perovskite solar cell according to claim 1, characterized in that The thickness of the hole transport layer is 5-15nm, the thickness of the perovskite active layer is 600-700nm, the thickness of the active layer interface modification layer is 5-20nm, the thickness of the electron transport layer is 40-80nm, the thickness of the cathode modification layer is 1-6nm, and the thickness of the cathode is 120nm.

4. The inorganic passivation layer modified perovskite solar cell according to claim 1, characterized in that The active layer interface modification layer is obtained by dissolving ammonium persulfate in isopropyl alcohol (IPA) and trifluoroethanol (TF-EtOH) to form a saturated solution at room temperature, then spin-coating the solution on the perovskite active layer and annealing at 100°C for 5 minutes.

5. A method for preparing a perovskite solar cell modified with an inorganic passivation layer according to any one of claims 1 to 4, characterized in that The following steps are involved: A positive substrate is selected and cleaned, and a hole transport layer, a perovskite active layer, and an active layer interface modification layer are spin-coated on the positive substrate from bottom to top, and an electron transport layer, a cathode modification layer, and a cathode are evaporated; wherein the active layer interface modification layer is a dense inorganic passivation layer of lead sulfate and lead oxide formed by spin-coating the strong oxidizing inorganic salt ammonium persulfate on the perovskite active layer to oxidize the excess lead iodide on the perovskite surface.

6. The method for preparing a perovskite solar cell modified with an inorganic passivation layer according to claim 5, characterized in that The hole transport layer is one of 2-pyrenyl-ethyl phosphoric acid, 2-(9H-carbazole-9-yl)ethylphosphonic acid, 2-(3,6-dimethoxy-9H-carbazole-9-yl)ethylphosphonic acid, and 4-(3,6-dimethyl-9H-carbazole-9-yl)butylphosphonic acid, which is spin-coated on the anode substrate.

7. The method for preparing a perovskite solar cell modified with an inorganic passivation layer according to claim 5, characterized in that The perovskite active layer is prepared by a one-step spin coating method of a perovskite precursor solution combined with an annealing treatment process. Specifically, after obtaining the perovskite precursor solution, a liquid phase one-step spin coating method is used to spin coat it on a flexible or rigid substrate with a carrier transport layer. After the spin coating is completed, it is heated at 120°C for 30 minutes.

8. The method for preparing a perovskite solar cell modified with an inorganic passivation layer according to claim 5, characterized in that The electron transport layer is one of a C60 film, a PCBM film and a SnOx film deposited on the active layer interface modification layer.

9. The method for preparing a perovskite solar cell modified with an inorganic passivation layer according to claim 5, characterized in that The negative modification layer is BCP deposited on the electron transport layer, and the cathode is a gold film or a silver film vacuum-thermally evaporated on the hole transport layer.

Citation Information

Patent Citations

  • Perovskite solar cell and preparation method thereof

    CN118338693A

  • Chemical molecule modified perovskite passivation structure, preparation method of solar cell, preparation method of light emitting diode and preparation method of photoelectric detector

    CN118870853A

Cited By

  • Preparation method of passivation layer, perovskite crystalline silicon laminated cell and manufacturing method thereof

    CN121174898A

  • Radiation-proof perovskite solar cell and space photovoltaic cell

    CN122121412A